The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2016
DOI: 10.3109/0886022x.2016.1149684
|View full text |Cite
|
Sign up to set email alerts
|

Safety and cardiovascular effects of mineralocorticoid receptor antagonists for patients receiving hemodialysis: a systematic review and meta-analysis

Abstract: Introduction Cardiovascular disease is an important factor in the mortality and morbidity of patients with end-stage renal disease receiving hemodialysis. Although mineralocorticoid receptor antagonists may have potential benefits on the cardiovascular system, their safety for patients on hemodialysis remains unclear, considering the differences between the results of already performed clinical trials. Methods MEDLINE, EMBASE, Cochrane, ClinicalTrials.gov and PubMed databases were searched for relevant clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 49 publications
1
2
0
Order By: Relevance
“…We noticed that previous published meta-analyses omitted important trials (e.g., there are only five RCTs in Zhao’s work ( Zhao et al, 2016 )), Zhao’s conclusion that MRA did not increase potassium levels significantly, this is consistent with our result. However, they did not analyze the effect of MRA on serum potassium in patients with different dialysis methods, we did a subgroup analysis specifically for this question.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We noticed that previous published meta-analyses omitted important trials (e.g., there are only five RCTs in Zhao’s work ( Zhao et al, 2016 )), Zhao’s conclusion that MRA did not increase potassium levels significantly, this is consistent with our result. However, they did not analyze the effect of MRA on serum potassium in patients with different dialysis methods, we did a subgroup analysis specifically for this question.…”
Section: Discussionsupporting
confidence: 91%
“…Notably, the risk/benefit ratio of MRAs in dialysis patients is less well defined, owing to concerns that their cardioprotective actions may be counteracted by excess risk of hyperkalemia ( Georgianos et al, 2017 ). Moreover, patients with end-stage renal disease often experience multiple complications, consequently, mineralocorticoid receptor antagonists (MRA) should be considered for complete blockade of the renin-angiotensin-aldosterone system (RAAS) ( Zhao et al, 2016 ). MRA, including eplerenone and spironolactone, have been shown effective in patients with hypertension and HFrEF ( Pitt et al, 1999 ; Zannad et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…From a clinical perspective, a direct association between intestinal MR and BP has not been established to date; however, several interesting studies have assessed the efficiency and safety of MR antagonists in dialysis patients 40, 41. In some, but not all, of these studies, BP improvement was observed using MR antagonists.…”
Section: Discussionmentioning
confidence: 99%